Physical and Cultural Environment of the Bundelkhand Region: The Impact of Population Growth on Development and Infrastructure in the Bundelkhand Region of Uttar Pradesh (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Uttar Pradesh with a population of 16.62 Crores is India’s most populist State. The economy of Uttar Pradesh is mostly dominated by agriculture and allied activities. UP-Bundelkhand region having 12.21 of the State’s area is under-populated with population density of 280 when compared to 690 in the State and 325 as National average. Little less than 5 of the State’s population lives there. The increasing size of population affects the growth in every sector of an economy. Every development programme is badly affected by massive increase in population. The increase in population in any region is not always in proportion to the increase in infrastructure.